Environmental, Social, and Governance (ESG) Disclosure Application to Company Profitability and Value - Fidyah Yuli Ernawati; Rita Andini; Heni Subekti (Universitas Negeri Semarang, 2025)
This study examined the impact of ESG disclosure implementation on manufacturing companies and their profitability, with capital structure as a mediating variable. This gap in research is due to several inconsistent findings with previous studies on the relationship between ESG disclosure and company performance, particularly in emerging markets like Indonesia. This study used quantitative analysis and PLS-SEM to examine 42 companies listed on the Indonesia Stock Exchange from 2018 to 2024. The results indicate that environmental, social, and governance disclosures positively affect company profitability, mediating the relationship between capital structure and ESG disclosure. These findings will contribute to understanding how ESG implementation affects company performance in emerging markets and provide practical insights for companies implementing ESG practices. These findings contribute to understanding the dynamics of ESG implementation in emerging markets, highlighting the influence of each ESG component on company performance. This study also emphasizes the importance of strategic alignment between sustainability initiatives and corporate financial management to optimize performance in the face of the ever-changing business landscape in Indonesia.